The Influence Of Leadership Style, Work Quality, Work Discipline And Career Development On Employee Performance At The West Bilah Subdistrict Office, Labuhanbatu Regency - Agnes Karina; Bayu Eko Broto; Yona Melia (International Journal of Economic Research and Financial Accounting, 2025)
This research aims to analyze the influence of leadership style, work quality, work discipline, and career development on employee performance at the West Bilah Subdistrict Office, Labuhanbatu Regency. This study applies a quantitative approach using purposive sampling techniques and survey methods to collect information from non-leadership staff. The research instrument was tested for validity and reliability, and analyzed using multiple linear regression. The research results identified that the four independent variables had a significant impact on employee performance simultaneously. However, partially, only work discipline was proven to have a significant and positive impact on employee performance (significance 0.000), while leadership style, work quality and career development did not show a direct significant effect. The coefficient of determination of 72.7% indicates that the four variables are able to explain most of the variation in employee performance. This research emphasizes the importance of increasing work discipline and structured career development in an effort to improve employee performance.